In situ coupling of atomic force microscopy and sub-micrometer focused X-ray techniques. Issue 1712 (14th October 2014) - Cornelius, Thomas W.; Ren, Zhe; Mastropietro, Francesca; Langlais, Simon; Davydok, Anton; Richard, Marie-Ingrid; Dupraz, Maxime; Verdier, Marc; Beutier, Guillaume; Boesecke, Peter; Thomas, Olivier
ABSTRACT: A scanning force microscope for in situ nanofocused X-ray studies (SFINX) has been developed which can be installed on diffractometers at synchrotron beamlines allowing for the combination with various techniques such as coherent X-ray diffraction and fluorescence. The capabilities of this device are demonstrated on Cu nanowires and on Au islands grown on sapphire (0001). The sample topography, crystallinity, and elemental distribution of the same area are investigated by recording simultaneously an AFM image, a scanning X-ray diffraction map, and a fluorescence map. Additionally, the mechanical response of Au islands is studied by in situ indentation tests employing the AFM-tip and recording 2D X-ray diffraction patterns during mechanical loading.